Improving student learning outcomes on SPLDV material using the Problem Based Learning model in class IX H SMPN 6 Surabaya - Suliswati Suliswati; Endah Budi Rahaju; Achmad Sahari; Lena Sucianita Muntiari (Jurnal Impresi Indonesia, 2024)
The problem based learning model is expected to be effective in enabling students to find solutions and solve their own problems, thereby increasing conceptual understanding of SPLDV material. The aim of this research is to find out how much influence the problem based learning model has on SPLDV material which can improve student learning outcomes at SMPN 6 Surabaya. This research uses the PBL method. The design of this research is a single case study, namely an experimental design by providing treatment to a small group and a large group. The results of data processing using the influence of the PBL learning model on the learning outcomes of conflict resources and social integration at SMPN 6 Surabaya. The result is the use of a problem-based learning model that involves sources of conflict which will improve student learning outcomes at SMPN 6 Surabaya. The use of the PBL learning model for learning outcomes related to SPLDV material at SMPN 6 Surabaya is classified as good, this can be seen from the average pre-cycle score carried out by individuals, namely 85.18, the average LKPD score is 1 learning outcome for small group students consisting of 2 participants. students is 85.90 and the average score for LKPD 2 student learning outcomes for a large group of 6 students is 99.09. In the collaborative classroom action research carried out it can be declared successful because there is an average increase in pre-cycle, cycle 1 and cycle 2 in learning outcomes.